Anti-Hyperalgesic Properties of Menthol and Pulegone - Hilfiger, Louis; Triaux, Zélie; Marcic, Christophe; Héberlé, Eléa; Emhemmed, Fathi; Darbon, Pascal; Marchioni, Eric; Petitjean, Hugues; Charlet, Alexandre (Frontiers in Pharmacology, 2021)
Context: Menthol, the main monoterpene found in Mentha piperita L (M. piperita). is known to modulate nociceptive threshold and is present in different curative preparations that reduces sensory hypersensitivities in pain conditions. While pulegone is a menthol-like monoterpene, only a limited number of studies focuses on its putative analgesic effects. Pulegone is the most abundant monoterpene presents in Calamintha nepeta (L.) Savi (C. nepeta), a Lamiaceae plant used in traditional medicine to alleviate rheumatic disorders, a chronic inflammatory disease. Objectives: Here, we analyzed the monoterpenes composition of extracts C. nepeta and M. piperita. We then compared the putative anti-hyperalgesic effects of the main monoterpenes found, menthol and pulegone, in acute inflammatory pain conditions. Methods: C. nepeta and M. piperita extracts were obtained through pressurized liquid extraction and analyzed by gas chromatography-mass spectrometry. The in vitro anti-inflammatory activity of menthol and pulegone were evaluated by measuring the secretion of the tumor necrosis factor from LPS-stimulated THP-1 cells. The in vivo anti-hyperalgesic effects of menthol and pulegone were tested on a rat model inflammatory pain model. Results: Pulegone and menthol are the most abundant monoterpene found in C. nepeta (49.41 %) and M. piperita (42.85 %) extracts, respectively. In vitro, both pulegone and menthol act as strong anti-inflammatory molecules, with EC50 values of 1.2±0.2 and 1.5±0.1 mM, respectively; and with a cytotoxicity with EC50 values of 6.6±0.3 and 3.5±0.2 mM, respectively. In vivo, 100 mg/kg pulegone exert a transient anti-hyperalgesic effect on both mechanical (pulegone: 274.25 ± 68.89 g, n=8; vehicle: 160.88±35.17 g, n=8, p <0.0001), thermal heat (pulegone: 4.09±0.62 s, n=8; vehicle: 2.25±0.34 s, n=8, p<0.0001) and cold (pulegone: 2.25±1.28 score, n=8; vehicle: 4.75±1.04 score, n=8, p=0.0003). In a similar way, 100 mg/kg menthol exert a transient anti-hyperalgesic effect on both mechanical (mechanical: menthol: 281.63±45.52 g, n = 8; vehicle: 166.25±35.4g, n = 8, p < 0.0001), and thermal heat (menthol: 3.65±0.88 s, n = 8; vehicle: 2.19±0.26 s, n=8, <0.0001). Conclusions: Here we show that both pulegone and menthol are anti-inflammatory and anti-hyperalgesic monoterpenes. These results might open the path towards new compound mixes to alleviate pain sensation.